REVEALING THE METHODS AND COMMENTARY FEATURES OF AL-QAULUL BAYAN FI TAFSIR AL-QUR’ĀN BY SYEKH SULAIMAN AR-RASULI - Ali Akbar; Jani Arni; Muslim Muslim; Aslati Aslati; Nurwahdi Nurwahdi (Jurnal Ushuluddin, 2019)
This article discusses the book of Tafsir al-Qaulul Bayan fi Tafsir al-Qur’ān by Syekh Sulaiman ar-Rasuli. This book is interesting to study because it is very rare to find interpreters using Minangkabau Malay Arabic. Syekh Sulaiman ar-Rasuli have specificity in writing his commentary because in his muqaddimah, it is stated that this book does not aim to explain and issue law. This expression is somewhat different from the purpose of the interpretation expressed by the commentators. This discussion aims to reveal the interpretation methods and patterns used by this book. The method used is content analysis: the purpose is to discuss in depth the written content or information. After reviewing this book, it can be concluded that this book uses the ijmali method. The interpretive style used is linguistic and Sufism feature. The feature of lughawi is to explain the meaning of the verse of al-Qur’ān with a linguistic approach, and the Sufism feature means to explain the meaning of the verse of al-Qur’ān with theories in Sufism or with a spiritual approach of the mufassir